Fish war [videorecording (DVD)] - Frank, Willie, III; Bennett Bill, Ramona, 1938-; Wilson, Althea (Virgil Films, 2024)
When the state of Washington banned tribes from fishing in their traditional waters and began arresting Indigenous fishers, it ignited the violent Fish Wars. FISH WAR chronicles their struggle, culminating in a landmark 1974 court ruling affirming treaty rights and making tribes co-managers of salmon. Yet, 50 years later, the fight for salmon in the Pacific Northwest continues.